Pengembangan dan pemberdayaan pengawas sekolah dari sudut pandang manajemen sumber daya manusia dan kebijakan yang berlaku - Sururi Sururi; Dedy Achmad Kurniady (Jurnal Abmas, 2014)
The successful implementation of a quality education is very closely tied to the success of improving the competence and professionalism of teachers and education personnel. The school superintendent /supervisor is one of the academic staff who holds an important and strategic role in improving the professionalism of teachers and quality of education in schools. The empowerment of schools superintendent who doesn't optimal, the low performance of the school superintendent and the weakness of the competency that is owned by the school superintendent are due to the being of violation of rules or policies by it management or bureaucracy which managed the school superintendent itself Whereas the rules and policies of the institution that houses the supervisor is clearly and completely from the process of recruitment, selection, performance appraisal, professional development, and performance accountability.